Hubungan Imunisasi BCG dengan Tuberkulosis Paru pada Anak Balita di RSUD Dr.Moewardi - Hidayat Fatahillah; Ismiranti Andarini; Dwi Hidayah (Fakultas Kedokteran, Universitas Sebelas Maret, 2022)
Background: Tuberculosis is still one of the main threats to public health as a cause of death from infectious diseases. One of the preventive efforts to prevent tuberculosis is the BCG immunization program, but the effectiveness of BCG immunization has decreased and the results differ in various research locations so it needs to be reviewed. This study aims to determine the relationship between BCG immunization and the incidence of pulmonary tuberculosis in children under five Methods: This research is an analytic observational design with a case control study conducted at RSUD Dr. Moewardi. Respondents in this study were divided into 2 groups, namely 30 case samples (pulmonary TB) and 30 control samples (non-pulmonary TB) where sampling was done by purposive sampling method. Samples were obtained from patient medical record data in the 2017-2019 period and then processed using SPSS 26 software Results: Based on the results of the bivariate analysis using the Fisher's Exact test, the correlation between phi (ρ) of 0.612 (α = 0.05) showed that there was no significant relationship between BCG immunization and pulmonary tuberculosis in children under five at Dr. Moewardi. Conclusion: There is no significant relationship between the provision of BCG immunization with the incidence of pulmonary tuberculosis in children under five at RSUD Dr. Moewardi Surakarta.